DevEx in Action. - Forsgren, Nicole; Kalliamvakou, Eirini; Noda, Abi; Greiler, Michaela; Houck, Brian; Storey, Margaret-Anne (Communications of the ACM, 2024)
This research article uses work design theory to investigate the work design of developers, with a focus on developer experience (DevEx) and how DevEx impacts outcomes of the individual developer, the team, and the organization overall. The hypotheses of this research looks at how flow state, feedback loops, and cognitive load positively impacts the three outcomes.